2014
DOI: 10.1039/c4nr02294g
|View full text |Cite
|
Sign up to set email alerts
|

Controllable copper deficiency in Cu2−xSe nanocrystals with tunable localized surface plasmon resonance and enhanced chemiluminescence

Abstract: Copper chalcogenide nanocrystals (CuCNCs) as a type of semiconductor that can also act as efficient catalysts are rarely reported. Herein, we study water-soluble size-controlled Cu(2-x)Se nanocrystals (NCs), which are copper deficient and could be prepared by a redox reaction with the assistance of surfactants. We found them to have strong near-infrared localized surface plasmon resonance (LSPR) properties originating from the holes in the valence band, and also catalytic activity of more than a 500-fold enhan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
95
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 103 publications
(103 citation statements)
references
References 52 publications
2
95
0
Order By: Relevance
“…The results showed that the atom ratios of Cu 2−x Se NPs and Cu 2−x Se/rGO/PVP nanofibers before and after annealing were about 1.70 (x = 0.30), 1.66 (x = 0.34), and 1.60 (x = 0.40), respectively, implying that Cu 2−x Se NPs still maintain the structure of high copper vacancy after electrospinning and post-treatment. 27,43 The above all mainly demonstrate the successful assembly of Cu 2−x Se on the rGO/ PVP hybrid nanofibrous mats.…”
Section: Acs Applied Materials and Interfacesmentioning
confidence: 93%
“…The results showed that the atom ratios of Cu 2−x Se NPs and Cu 2−x Se/rGO/PVP nanofibers before and after annealing were about 1.70 (x = 0.30), 1.66 (x = 0.34), and 1.60 (x = 0.40), respectively, implying that Cu 2−x Se NPs still maintain the structure of high copper vacancy after electrospinning and post-treatment. 27,43 The above all mainly demonstrate the successful assembly of Cu 2−x Se on the rGO/ PVP hybrid nanofibrous mats.…”
Section: Acs Applied Materials and Interfacesmentioning
confidence: 93%
“…While plasmonic nanosensors are almost exclusively made of gold or silver, LSPR sensing applications of other metal and/or metal oxide nanocomposites, e.g., zinc oxide [78][79][80], aluminium [81][82][83][84][85][86][87] and copper [88][89][90][91][92][93][94][95][96], have also been investigated. However, the non-noble metals are susceptible to corrosion in aqueous environments and oxidation in air, both of which significantly diminish refractive index sensitivity [4].…”
Section: Effect Of Nanoparticle Composition Size and Shape On Plasmomentioning
confidence: 99%
“…[1][2][3][4] Especially, copper sulfide (CuS), a member of the transition metal chalcogenides, which is an important family of p-type semiconductors with superior optical, electrical, and other physical and chemical properties, has been extensively studied for its applications in the areas of lithium batteries and solar cells, [5][6][7][8][9] sensing, [10][11][12][13][14][15][16] photothermal therapy, [17][18][19][20] imaging, 21,22 supercapacitance, 23,24 drug delivery, 25 cathode materials, 26 nonlinear optical materials, 27 and catalysis. [1][2][3][4] Especially, copper sulfide (CuS), a member of the transition metal chalcogenides, which is an important family of p-type semiconductors with superior optical, electrical, and other physical and chemical properties, has been extensively studied for its applications in the areas of lithium batteries and solar cells, [5][6][7][8][9] sensing, [10][11][12][13][14][15][16] photothermal therapy, [17]…”
Section: Introductionmentioning
confidence: 99%